Study of ovarian cancer at a tertiary care centre - Mulik, Jayashree; Khadse, Swapnil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Despite major advances in case management, ovarian cancer continues to have the highest case fatality rate of all gynaecologic malignancies. There is paucity of meaningful screening and diagnostic protocols. Present study was planned with the objective of assessment of the prevalence of ovarian cancer and the associated risk factors at a tertiary care centre. Methods: The present prevalence study was conducted at a tertiary care government hospital and entailed analysis of data of 73 patients of ovarian cancer. All the participants were subjected to comprehensive history taking, followed by general, systemic, per-speculum and per-vaginal examination. Serum tumour markers of the patients were assessed. Imaging studies including ultrasound, CT or MRI abdomen/pelvis were done as per need. Final diagnosis was confirmed on histopathology and the cases were classified according to histological classification of World Health Organization. Results: Majority (41, 56.2%) were aged more than 45 years and above, most of them with one to two previous issues (64.3%). The disease was observed to be more common in postmenopausal women (65, 89%). Three fourth participants had negative family history of ovarian or breast cancer. Out of 73 patients, 31 had value of CA 125 between 150-400 U/mL and 42 had values >400 U/mL. Epithelial ovarian cancer (serous- 33, 45.2%, mucinous- 18, 24.7%) was observed to be the commonest histological type. Conclusions: To diagnose ovarian tumours early using multipronged approach with focussed risk factor identification and screening with CA-125 is very important and is strongly recommended.